(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Clinical ethics committees are bodies that provide bioethics advice to healthcare professionals working in hospitals and promote the culture of bioethics within a certain community. Italian legislation has not yet set out general rules for the nature and functions of these bodies whose role is becoming increasingly important due to biomedical technical progress, the raising of ever more complex problems in modern medicine from a clinical, ethical, legal standpoint, and the spread of moral and cognitive pluralism on bioethical issues. In the practical experience, where regional regulations are not available, normative frameworks of these committees have been established moulding case by case the applicable law. In this legislative vacuum, regulatory experimentation has been rich and manifold, but the absence of national rules has resulted in the disempowerment of the functions carried out by the clinical ethics committees. Indeed, the lack of national normative is likely to decrease, above all, those public and promotional committee functions aimed at enhancing and disseminating bioethical knowledge among the healthcare professionals and among the public in general by benefiting those communities living in the areas of hospitals within which the clinical ethics committees perform their duties.